GAMBARAN PENGETAHUAN PERAWATAN PALIATIF PADA PERAWAT ICU DI RSUD ULIN BANJARMASIN - Anissa, Anissa; Hafifah, Ifa; Nasution, Tina Handayani (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p06, 2022)
Palliative care is given since the diagnosis is made so that physical, psychosocial and spiritual problems can be addressed early. Nurses are one of the health workers who play an important role, lack of palliative knowledge will lead to a lack of care services provided. This study aims to represent the knowledge of palliative care in ICU nurses at Ulin Hospital Banjarmasin. The method used is descriptive quantitative. The sampling technique used was non-probability sampling with purposive sampling. The research sample was 32 nurses in the intensive room of Ulin Hospital Banjarmasin. The instrument used a demographic data sheet and a PCQN-I questionnaire. Univariate data analysis is a method of analyzing data. The results revealed that 21 people (65,6%) in the low knowledge category and 11 (34,4%) in the moderate knowledge category. Most of the respondents had never attended palliative training and did not understand the general concept of palliative.